Laser-induced breakdown spectroscopy analysis of human deciduous teeth samples. Issue 9 (December 2015) - Khalid, Arooj; Bashir, Shazia; Akram, Mahreen; Hayat, Asma
Abstract Laser-induced breakdown spectroscopy (LIBS) analysis of human deciduous teeth has been performed by employing Nd:YAG laser (1064 nm, 10 ns) for the evaluation of plasma parameters as well as elemental analysis. The plasma parameters, i.e., electron temperature and electron number density of laser-induced teeth plasma at various fluencies, have been evaluated. Both parameters show an increasing trend up to a certain value of laser fluence, i.e., 2.6 J/cm2 . With further increase in laser fluence up to a value of 3.9 J/cm2, a decreasing trend is observed which is due to shielding effect. With further increase in laser fluence up to a maximum value of 10.5 J/cm2, the insignificant changes in plasma parameters are observed which are attributed to saturation phenomenon governed by self-regulating regime. Emission spectroscopy results exhibit that laser fluence is the controlling factor for both plasma parameters. The elemental analysis was also performed at constant laser fluence of 2.6 J/cm2 by evaluating the variation in detected elemental concentration of Ca, Fe, Sr, Zn, and Pb in three different parts of human teeth, i.e., enamel, dentine, and cementum. The lower concentration of Ca as compared to the standard values of CaCO3 (self-fabricated pellet) reveals that enamel is the most deciduous part of the human teeth. However, at the same time, it is also observed that the highest concentration of micro minerals is also found in enamel, then in dentine, and lowest in cementum. Carious or unhealthy tooth is identified by enhanced concentration of micro minerals (Pb, Sr, Zn, and Fe). The highest concentration of micro minerals as compared to other parts of teeth (dentine and root cementum) and lower concentration of Ca as compared to standard CaCO3 pellet in enamel confirm that enamel is the most deciduous part of the teeth.